The hazardous waste generated in the Peruvian textile industry: Haute couture, alpaca fiber and tannery - Huiman Cruz, Español (2022)
The research cites the various hazardous waste generated in the textile industry. The method used is descriptive and comparative, the process consisted of the search and evaluation of information, both nationally and internationally. The results indicate: (1) Waste is generated from the alpaca fiber industry in the various stages of camelid rearing, they stand out for their dangerousness: excreta, residual fiber and yarn scraps. (2) The main hazardous waste generated by the tannery industry are: grease, hides, hair, plastic containers with traces of toxic substances, chips and pieces of leather with chrome. (3) Three companies' Solid Waste Management Plans were analyzed, randomly selected, and none of them detail waste treatment processes and warn of the lack of supervision by the authorities. It is concluded that the hazardous waste generated can affect human and environmental health. On the other hand, there is the possibility of taking advantage of certain hazardous waste such as manure and alpaca fiber, after treatment; while non-hazardous waste from the tannery such as yarn, panel weaving, cloth, scraps and thread; can be used to produce new products, generating a production chain in favor of the entrepreneur himself.